Deixis analysis on Imagine Song by John Lennon - Aura Akmalia Yudanti; Rawuh Yuda Yuwana (Musamus Journal of Language and Literature, 2024)
Deixis refers to the research of using spoken or written language to indicate or indicate something specific. This research aims to analyze the deixis used in a song by John Lennon entitled Imagine and to understand the meanings this deixis conveys. This research used a qualitative approach with content analysis. The analysis was performed using the Dexis theory proposed by Yule. The results show that there are three categories of deixis found in the data: personal, spatial deixis, and temporal deixis. Among them, personal deixis is the most common, followed by spatial deixis, and temporal deixis is the least used. Moreover, data analysis shows that the person deixis plays a role in revealing by whom the sentence is uttered and to whom it refers. Spatial definitions are used to clarify sentences regarding word location and reference. On the other hand, temporal deixis is used to give timing and description of events. In conclusion, using deixis in song allows people to convey clear information about who is speaking, where the conversation occurs, and when it will occur.